THE CURRENT ECONOMIC SITUATION IN THE CIS REGION: BETWEEN CRISES? - BUDKIN, Viktor (CENTRAL ASIA AND THE CAUCASUS, 2013)
This article examines the specific manifestations of crisis phenomena in the region of the Commonwealth of Independent States (CIS) that are most pronounced in countries making progress in the creation of a market economy. The author emphasizes the imitative nature of economic reforms in the post-Soviet space. Based on an analysis of international assessments of the current economic situation in these states, he identifies the main factors that prevent their transition from extensive to intensive economic activity. He stresses the objective nature of the lack of internal prerequisites for a transition to large-scale modernization of the economy and innovative economic development. His conclusion is that the CIS countries (or "newly independent states" in foreign terminology) may face high-level threats to national security with the onset of the next stage of the recession in the absence of reliable prerequisites for economic stabilization in these countries.